Quantum codes from skew constacyclic codes over the ring Fq[u,v]∕〈u2−1,v2−1,uv−vu〉 - Tushar Bag (2020)
© 2019 Elsevier B.V. In this paper, we study quantum error-correcting codes from skew constacyclic codes over the ring [Formula presented], where q=pm for any odd prime p and positive integer m. We decompose skew constacyclic codes over the ring R as a direct sum of skew constacyclic codes over Fq. Self-dual skew constacyclic codes over the ring R are characterized. Necessary and sufficient conditions for skew negacyclic and skew constacyclic codes to be dual-containing are obtained. As an application, we construct new quantum error-correcting codes from skew constacyclic codes over Fq.